ONLINE TO OFFLINE: ROLE OF INSTAGRAM MARKETING ON INTENTION TO VISIT ART GALLERIES - Chhabra, Neha Kaur (ShodhKosh: Journal of Visual and Performing Arts, 2023)
The advancement of information and communication technologies is widely acknowledged as a crucial contributor to cultural influence. Social media platforms such as Instagram and Facebook offer innovative ways to share digitized images and videos effortlessly, at no cost, and in real time. The emergence of social media marks a significant milestone in the digital marketing era. This study examines the comparative effectiveness of Instagram ads over traditional newspaper ads. The effectiveness of these marketing strategies was assessed through a survey measuring respondents’ perceptions and intentions to visit an art gallery. The results, analysed using an independent samples t-test, revealed a statistically significant difference in perception scores between the two groups. Respondents exposed to the Instagram ad reported significantly higher positive intentions compared to those who viewed the newspaper ad. This finding highlights the superior impact of digital marketing, particularly on visually driven platforms like Instagram, which aligns well with the aesthetic nature of art galleries. The study underscores the importance of embracing digital marketing strategies in the art sector, suggesting that Instagram ads can more effectively engage audiences and enhance gallery visibility compared to traditional methods. However, it also recommends a balanced marketing approach that integrates both digital and traditional channels to reach a broader and more diverse audience. The research provides valuable insights for art galleries aiming to adapt to the evolving digital landscape.